Exploring the α2-adrenergic receptors with alkyl substituted bis-guanidinium diaryl derivatives - Hyland, Roisin (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
The burden of mental health conditions is on the rise globally. It is well documented that noradrenaline has a key role in memory, attention, stress, and regulation of emotions. The α2-adrenergic receptors (α2-ARs) are an attractive biological target for therapies for neurological conditions. Thus, α2-AR antagonists would block the activation of this autoreceptor potentially operating as therapeutic antidepressant agent. In a ligand-based drug design strategy we have investigated the effects on the binding affinity and ligand-receptor functional activity when releasing the rigid 2-aminoimidazolium moiety of lead compound 1, thus affecting steric and lipophilic properties. This aim will be achieved via computational studies, synthesis, and pharmacological evaluation. Due to their relevance in depression, three inactive α2A-AR receptor templates were used in the docking study: a homology model developed by Prof. Olivella, and two crystal structures recently reported, one complexed with a partial agonist and another with an antagonist. Compounds 1 (lead, symmetric), 15 (asymmetric), 16 (asymmetric), 18 (symmetric) and 22c (symmetric) were used as ligands for standard rigid receptor and fit-induced docking studies. All docked compounds were orientated based on the ionic interaction with the aspartate residue D1133.32, a known critical anchoring interaction with the α2-AR binding sites. Agonists 15 and 18 show interactions with S2005.42, a known residue involved in agonist activity, Moreover, the interaction between the ligand and E942.65 is common to the two known antagonists 16 and 22c and this could assist in directing the ligand away from TM5, avoiding receptor activation. A new synthesis of di-Boc-protected mono-substituted thioureas was developed utilizing Mitsunobu reaction conditions. Additionally, five new compounds were prepared, characterised using 1H and 13C NMR, IR, and HRMS. The α2-AR binding affinities of these compounds were measured in human prefrontal cortex tissue using a competitive assay with the α2-AR selective radioligand [3H]RX821002. When the ligands showed α2-AR affinity with Ki < 100 nM, functional [35S]GTPγS assays were used to determine their activity (i.e. antagonist, agonist or inverse agonist). Encouragingly, one of the five newly synthesised compounds (22c) displayed a binding affinity of 95.50 nM (best of substituted bis-guanidinium ligands to date) and antagonist activity. Considering past and present results with compounds 1, 16, 17 and 22c, a derivative containing both an imidazolium moiety and an ethyl-substituted guanidinium could be a very promising high affinity antagonist.
APPROVED
Keywords: alpha-2 adrenergic receptor; allkyl substitution; guanidines; mitsunobu reactions; computational chemistry; antagonist